Wife consultant - Ayeah, Colin Diyen (Langaa Research & Pub., 2012)
Some men believe that they own the world and that women are simply objects placed in that world to enable men to enjoy it fully. Such men claim to fully understand what is on a woman's mind at every moment, an indication of control over the female sex, and proof of their opinion that a woman's happiness depends fully on the man. Do men really understand and know as much about women as they presume? In this book, the author imagines himself as a woman and tries to think like one. It is left for the women to see whether the real image of a woman has been presented.